Prevalence of impaired fasting glucose and associated risk factors among Malaysian adult population: Findings from the National Health and Morbidity Survey (NHMS) 2019 - Murnizar Mokhtar; Nor Azian Mohd Zaki; Nurul Huda Ibrahim (PLoS ONE, 2025)
Impaired fasting glucose (IFG) is a condition when a person’s blood glucose level is above the normal range, but below the diagnostic cut-off for a formal diagnosis of diabetes mellitus. The objective of this study was to determine the prevalence of IFG among adults aged 18 years and older in Malaysia and its’ associated factors. Data were obtained as part of the National Health and Morbidity Survey (NHMS) 2019 [1]. It was a community-based, cross-sectional study that was conducted among a targeted population in both urban and rural areas in all 13 states and 3 federal territories in Malaysia, using a two stage stratified random sampling method. Adults aged 18 years and older with fasting capillary blood glucose (FBG) readings of ≤ 6.9 mmol/L were selected, except those known to have diabetes. IFG was defined according to World Health Organization (WHO) criteria as FBG between 6.1 and 6.9 mmol/L. The data were analyzed using SPSS Version 28.0. A total of 6183 respondents - 2842 men and 3341 women participated in this study. The overall prevalence of IFG was 22.6% (95% CI: 20.4, 24.9). Respondents aged 60 years and older had the highest percentage of IFG at about 30.2% (95% CI: 26.4, 34.4), followed by respondents with hypercholesterolemia at 29.2% (95% CI: 25.2, 33.6) and respondents with hypertension at 27.7% (95% CI: 24.3, 31.4). Multivariate analysis revealed that age of 60 years and above (aOR 1.51, 95% CI: 1.01, 2.06) and marriage (aOR 1.46, 95% CI: 1.16, 1.84) were significantly associated with IFG. The prevalence of IFG among Malaysian adults according to data obtained in 2019 was 22.6%, with an age of 60 and above and married being the associated factors. Policies need to be tailored for more vigorous screening among this group for prompt diagnosis and treatment to prevent complications.